HOUT-14. HOMOLOGOUS RECOMBINATION DEFICIENCY IN PATIENTS WITH HIGH GRADE GLIOMAS. (5th November 2018) - Krutz, Matthew; Mcginnis, Austin; Osborn, Kelley; Vesely, Sara; Vidal, Gabriel; Sung, Sarah; Ramkissoon, Shakti; Battiste, James
Abstract: Patients with Homologous Recombination Deficits (HRD) have shown increased survival in many cancers. With PARP inhibitors surfacing as a potential therapy for Glioma patients, we aim to explore the existence of HRD and its prognostic value in High-Grade Glioma patients. We conducted a chart review of patients with Gliomas who received Foundation One testing at The University of Oklahoma from 2013 to 2018. We used Foundation Ones Loss of Heterozygosity (LOH) score as a measure for HRD. We analyzed the correlation between the existence of mutated IDH and the LOH score. We then analyzed the significance of receiving Foundation One testing prior to any treatment on LOH score. Finally, we separated the patient population into two groups, High-HRD (>5% LOH or >3% LOH) and Low-HRD (<5% LOH or <3% LOH), and used the Kaplan-Meier method to assess OS and PFS. 39 patients were included in the final analysis. The relationship between IDH status and LOH score approached significance (P=.09). The relationship between time of foundation testing and LOH score was statistically significant (P=.05). In analyzing survival, we were only able to find significance in patients who received genetic testing post-treatment. Interestingly, the average OS of the Low-HRD group was 19 months, compared to 52 months for the High-HRD population which was statistically significant (p=.02). There appears to be a relationship between IDH status and HRD and although it was not yet statistically significant, it approached significance. Patients tested in a recurrent setting were more likely to possess higher HRD. We found no statistically significant difference in PFS or OS between the low-HRD and high-HRD populations, except in the later stage patient population. Due to the difference in the average PFS and OS this should be studied further in a larger population.